2013
DOI: 10.1590/s1516-89132013005000014
|View full text |Cite
|
Sign up to set email alerts
|

Generation of intensity duration frequency curves and intensity temporal variability pattern of intense rainfall for Lages/SC

Abstract: The objective of this work was to analyze the frequency distribution and intensity temporal variability of intense rainfall for Lages/SC from diary pluviograph data. Data on annual series of maximum rainfalls from rain gauges of the CAV-UDESC Weather Station in Lages/SC were used from 2000 to 2009. Gumbel statistic distribution was applied in order to obtain the rainfall height and intensity in the following return periods: 2, 5, 10, 15 and 20 years. Results showed intensity-duration-frequency curves (I-D-F) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Longer return periods increased rainfall intensity (Figs. 2-3), as observed by other authors (Elsebaie, 2012; Cardoso et al, 2014;Tfwala et al, 2017).…”
Section: Rainfall Intensitysupporting
confidence: 83%
See 2 more Smart Citations
“…Longer return periods increased rainfall intensity (Figs. 2-3), as observed by other authors (Elsebaie, 2012; Cardoso et al, 2014;Tfwala et al, 2017).…”
Section: Rainfall Intensitysupporting
confidence: 83%
“…Otherwise, rainfall intensity dropped to 9 and 10 mm h -1 , respectively, for Barreiras and Colinas, when the rainfall had a duration of 24 hours. The reduction of rainfall intensity with longer raining period is an expected tendency, but the intensity was related with local climate (Elsebaie, 2012;Cardoso et al, 2014;Tfwala et al, 2017). For example, Elsebaie et al (2012) observed maximum rainfall intensity reducing from 38 mm h -1 in 10 minutes, to 1.74 mm h -1 in 24 hours, for return period of two years in Najran region, Saudi Arabia.…”
Section: Rainfall Intensitymentioning
confidence: 96%
See 1 more Smart Citation
“…The IDF curve method has gained a large prominence through different study all over the world (e. g. Jakob et al, 2007; Xu and Tung, 2009; Lee et al, 2010; Haddad et al, 2011; Dourte et al, 2013; Du et al, 2014), they were applied on Yangambi station in Congo, using precipitation series in conjunction with Montana method, the results uncovered advantages and the inconvenient of the classical Montana formula, which did not lead to a satisfying result regarding the probabilistic and physical-based approach [11]. Further a study carried out in the south of Quebec, compared two different estimators of IDF curves, using the partial duration series (SDP) and the series of annual maxima (SMA) [12], Another study was performed in Brazil, aims to analyze the temporal distribution for intense rainfall and develop an IDF equation [13]. Munshi Md.…”
Section: Rainfall Intensity-duration-frequency Methodsmentioning
confidence: 99%
“…First established in 1932 by Bernard [17], IDF is a statistical relationship of the intensity, duration and frequency of rainfall derived from historical rainfall data [13,16,22]. Since then, many different sets of relationships have been constructed for different parts of the world [13,16,17,[22][23][24][25].…”
Section: Rationalementioning
confidence: 99%